Pengaruh Penerapan E-commerce dan Financial Literacy Terhadap Kinerja Keuangan UMKM : Studi Kasus UMKM di Kota Bandar Lampung - Sanny Ariwianto; Endah Yuni Puspitasari; Dian Nirmala Dewi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
In the era of globalization, many new business innovations have emerged, including Micro, Small, and Medium Enterprises (MSMEs), which play a significant role in Indonesia's economic growth. However, MSMEs face obstacles such as suboptimal use of technology and low levels of financial literacy. This study examines the impact of e-commerce adoption and financial literacy on the performance of MSMEs in Bandar Lampung City, using 115 respondents selected by purposive sampling method. Hypothesis testing using multiple linear regression shows that the adoption of e-commerce and financial literacy simultaneously affect MSME performance by 37.3%, with both having a positive impact on MSME performance. This means that the better the e-commerce adoption and financial literacy, the better the performance of MSMEs.